PENDIDIKAN KARAKTER BERBASIS AL-QUR'AN: KAJIAN KONSEP ULUL ALBAB PADA SEKOLAH DASAR - Arzaqi, Anindhya Faza; Khudori Soleh, Achmad (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This research examines the application of the Ulul Albab concept in Qur'an-based character education in elementary schools. Ulul Albab refers to individuals with a balance of intellectual, spiritual, and emotional intelligence. This research method is a literature review that analyzes various sources related to the concept of Ulul Albab and Islamic character education. The results showed that this concept can be integrated in the curriculum through a holistic approach and Qur'anic values, although there are challenges such as limited resources and variations in concept understanding. However, there are opportunities for development through comprehensive teaching materials, cooperation between schools, and teacher training. Ulul Albab-based character education has the potential to strengthen students' character building according to Islamic values.